Implementing the Bond Convergence Trade in South Africa - Matshoba, Nomathibana Z (School of Economics, 2014)
Convergence trade, by definition, is buying an asset now to be delivered at some date in the future and selling a similar asset, to be delivered at the same future date, at a higher price. In this paper, implementation of bond convergence trade is explored in the South African market. This is in spite of the features of the South African bond market. The South African bond market is significantly different from markets where bond convergence trade has previously been tested. Duration was subsequently introduced in identifying similarities between bonds, and this is the major difference introduced compared to prior work in the literature. The results showed that the trades give, on average, negative returns. However, further investigation into the impact of interest rates not only on the trade, but over the period of investigation and future expected interest rates, is required, before the results can be appropriately interpreted.